Historiography and the formation of philosophical canons
1 online resource
Keywords: "This book presents a series of case studies and reflections on the historiographical assumptions, methods, and approaches that shape the way in which philosophers construct their own past. The chapters in the volume advance discussion of the methods of historians of philosophy, while at the same time illustrating the various ways in which philosophical canons come into existence, debunking the myth of analytical philosophy's ahistoricism, and providing a deeper understanding of the roles historiographical devices play in philosophical thought. More importantly, the contributors attempt to understand history of philosophy in connection with other historical and historiographical approaches: contributors engage classical history of science, sociology of knowledge, history of psychology and historiography, in dialogue with historiographical practices in philosophy more narrowly construed. Additionally, select chapters adopt a more diverse perspective, by making place for non-Western approaches and for efforts to construe new philosophical narratives that do justice to the voice of women across the centuries. Historiography and the Formation of Philosophical Canons will be of interest to researchers and advanced students working in history of philosophy, meta-philosophy, philosophy of history, historiography, intellectual history, and sociology of knowledge"--